GATA3 acts upstream of FOXA1 in mediating ESR1 binding by shaping enhancer accessibility - Theodorou, Vasiliki (Cold Spring Harbor Laboratory Press, 2013)
Estrogen receptor (ESR1) drives growth in the majority of human breast cancers by binding to regulatory elements and inducing transcription events that promote tumor growth. Differences in enhancer occupancy by ESR1 contribute to the diverse expression profiles and clinical outcome observed in breast cancer patients. GATA3 is an ESR1-cooperating transcription factor mutated in breast tumors; however, its genomic properties are not fully defined. In order to investigate the composition of enhancers involved in estrogen-induced transcription and the potential role of GATA3, we performed extensive ChIP-sequencing in unstimulated breast cancer cells and following estrogen treatment. We find that GATA3 is pivotal in mediating enhancer accessibility at regulatory regions involved in ESR1-mediated transcription. GATA3 silencing resulted in a global redistribution of cofactors and active histone marks prior to estrogen stimulation. These global genomic changes altered the ESR1-binding profile that subsequently occurred following estrogen, with events exhibiting both loss and gain in binding affinity, implying a GATA3-mediated redistribution of ESR1 binding. The GATA3-mediated redistributed ESR1 profile correlated with changes in gene expression, suggestive of its functionality. Chromatin loops at the TFF locus involving ESR1-bound enhancers occurred independently of ESR1 when GATA3 was silenced, indicating that GATA3, when present on the chromatin, may serve as a licensing factor for estrogen–ESR1-mediated interactions between cis-regulatory elements. Together, these experiments suggest that GATA3 directly impacts ESR1 enhancer accessibility, and may potentially explain the contribution of mutant-GATA3 in the heterogeneity of ESR1+ breast cancer.